GENDER REPRESENTATION IN THE TWO EFL TEXTBOOKS IN INDONESIAN SENIOR HIGH SCHOOL: A SYSTEMIC FUNCTIONAL LINGUISTIC ANALYSIS - Indah Mutimatul Maufiroh, - (2020)
This paper is concerned with gender representation in the two EFL textbooks, specifically in Indonesian context. The framework of systemic functional linguistic proposed by Halliday and Matthiessen (2014) is utilized in this study. The processes in the texts find out that there is gender bias in the two texbooks i.e. material process and attributive process. In the material process, male characters are associated with skills/knowledge related activities, while female characters are associated with domestic activity. Meanwhile, in attributive processes, physical appearances and traits of female characters are highlighted, while male characters do not appear. In relation to reveal the authors' view realized in the representation of gender in the textbooks, in essence, the authors know about gender sensitivity and awareness but they are not always applicable in the textbooks. Makalah ini berkaitan dengan representasi gender dalam dua buku Bahasa Inggris, khususnya dalam konteks Indonesia. Kerangka kerja linguistik fungsional sistemik yang diusulkan oleh Halliday dan Matthiessen (2014) digunakan dalam penelitian ini. Proses dalam teks menemukan bahwa ada bias gender dalam dua buku yaitu proses materi dan proses atributif. Dalam proses materi, karakter laki-laki dikaitkan dengan kegiatan keterampilan / pengetahuan, sedangkan karakter perempuan dikaitkan dengan aktivitas rumah tangga. Sementara itu, dalam proses atributif, penampilan fisik dan ciri-ciri karakter perempuan lebih disorot, sedangkan karakter laki-laki tidak muncul. Sehubungan dengan mengungkapkan pandangan penulis yang diwujudkan dalam representasi gender dalam buku teks, pada dasarnya, penulis tahu tentang sensitivitas dan kesadaran gender tetapi apa yang diungkapkan penulis tidak mucul dalam buku teks.